Selecting Green Wall Adoption Best Solutions Using Optimization: Addressing Barriers and Maximizing Benefits - Nadeem, Samar (AUC Knowledge Fountain, 2025)
This research explores the potential of green walls as a sustainable solution to mitigate urban challenges and align with global climate change objectives. Despite their ecological and social benefits, green wall implementation faces significant barriers, hindering their adoption. Consequently, this study aims to develop a comprehensive framework to identify the obstacles, propose feasible solutions, and provide actionable strategies for promoting green walls. This framework incorporates an optimization model specifically designed for government-led solutions, evaluating their feasibility based on administrative feasibility, community acceptance, technical feasibility, industrial acceptance, and long-term adoption potential. By quantifying and prioritizing solutions based on their cost, feasibility, and multi-dimensional impacts, the model ensures their applicability within real-world constraints. This aspect makes the framework highly relevant for supporting governmental bodies and decision-makers in constructing practical, resource-efficient plans to promote green walls. To achieve this, the research employed a combination of literature review, and focus group discussions for data gathering process. The findings revealed widespread agreement on key barriers, which were validated through stakeholder perspectives and the literature. These barriers include high initial costs, lack of public awareness, inadequate maintenance planning, and the absence of mandatory policies for the integration of green walls. These barriers hinder adoption, particularly in regions like Cairo, Egypt, where urban sustainability is crucial. Moreover, the optimization model was designed to reflect real-life complexities, accounting for financial, social, environmental, and technical factors. The outcomes highlight the model’s effectiveness in representing real-world conditions by aligning solutions with stakeholder priorities and resource limitations. By providing a structured and scalable approach to decision-making, this research not only addresses Cairo’s unique needs but also offers a guiding framework for governmental bodies in other regions and cities. The framework enables decision-makers to promote green walls effectively, contributing to sustainable development goals and fostering their wider adoption in urban contexts globally.